HUBUNGAN ANTARA KONTROL DIRI DENGAN PERILAKU MENYONTEK PADA SISWA KELAS X SMA NEGERI 3 PEMALANG - Nela Agistiani; Tri Suyati; G. Rohastono Ajie (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
This research was motivated by students' low self-control. One of the causes of students engaging in cheating behavior is students' low self-control. The formulation of the problem in this research is, is there a relationship between self-control and cheating behavior in class X students at SMA Negeri 3 Pemalang?" The aim of this research is to determine the relationship between self-control and cheating behavior in class X students at SMA Negeri 3 Pemalang.This type of research is quantitative research with a correlational research design. The population of this research data is 288 students, including classes X. 1, X. 2, X. 3, X. 4, X. 5, X. 6, X. 7, X. 8. 36 class X students. 7. The sample in this study was 72 students taken using cluster random sampling technique. The data collection tools used were the Self Control Scale and the Cheating Behavior Scale.The results of the person product moment hypothesis test show that the person product moment correlation test of the two variables obtained significant results of (r) = -0.474. Meanwhile, the r table value for a sample size of 72 with a significance level of 5% is 0.229, which means the two variables have a significant relationship. Therefore, the calculated r value -0.474 > 0.229, when compared with the interpretation table, shows that the self-control variable and the cheating behavior variable have a moderate level of relationship. These results show that there is a relationship between self-control and cheating behavior in class X students at SMA Negeri 3 Pemalang.